(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Aim: Present study was designed to determine the effect of acetate and Selective serotonin reuptake inhibitors (SSRI) on stress and blood lipid profile in stressed rat. Materials and Methods: Animals were divided in 5 groups (n=6) , treated with 20 mg/kg p.o. of Fluoxetine (SSRI) and glyceryl triacetate (GTA) at 6g/kg p.o dose (acetate supplementation) alone and in combination. for 28 days to assess its effect in immobilized stressed rats. Open field and Hole board test were used for determination of stress in animals followed by blood lipid level. Results: Animals treated with 20 mg/kg p.o Fluoxetine (SSRI), 6 g/kg p.o GTA and SSRI (Fluoxetine) + GTA showed significant (p<0.01) stress resistant activity as compared to negative control. Results also demonstrated that there was significant (p<0.01) decrease in blood lipid level in animals treated with 20 mg/kg p.o Fluoxetine (SSRI), 6 g/kg p.o GTA and SSRI (Fluoxetine) + GTA. Conclusion: Present study concludes, Acetate and SSRI supplementation posses stress resistant and antihyperlipidemic potential in immobilized stressed rats may be by enhancing the acetylation of histone.